Association of a large vulvar tumor in a young premenopausal woman with recurrent pseudoangiomatous stromal hyperplasia of the breasts - Knickerbocker, Angelica M.; Timmons, Douglas; Tjendra, Youley; Garzon, Simone; Carugno, Jose (Archive of Oncology, 2019)
Pseudoangiomatous stromal hyperplasia is a benign proliferative lesion of the breast tissue that typically affects women in the reproductive age. Pseudoangiomatous stromal hyperplasia usually presents as a localized, painless, firm mass or as a diffuse thickened area of the breast. Rarely, it can arise along the embryonic milk line, up to the anogenital region, where it simulates angiosarcomas. Awareness of this uncommon condition is important in order to avoid unnecessary aggressive excisional surgical procedures. For this purpose, we present a case of nodular pseudoangiomatous stromal hyperplasia arising in the vulva in a patient with recurrent pseudoangiomatous stromal hyperplasia of the breast.
Keywords: Diagnosis; Immunosuppression; Pseudoangiomatous stromal hyperplasia; Breast; Vulva